Security analysis (New York McGraw-Hill, 1996)
Explains financial analysis techniques, shows how to interpret financial statements, and discusses the analysis of fixed-income securities and the valuation of stocks.
Includes index.
Reprint of first ed. Originally published: New York : Whittlesey House, 1934.
Keywords: Investment analysis; Securities -- United States; Speculation; Dividendes; Investissements; Spâeculation.; Valeurs mobili?eres -- Cours